Homogeneous cooling state of dilute granular gases of charged particles - Takada, Satoshi; Serero, Dan; Pöschel, Thorsten (Physics of Fluids, 2017)
We describe the velocity distribution function of a granular gas of electrically charged particles by means of a Sonine polynomial expansion and study the decay of its granular temperature. We find a dependence of the first non trivial Sonine coefficient, a2 , on time through the value of temperature. In particular, we find a sudden drop of a2 when temperature approaches a characteristic value, T∗, describing the electrostatic interaction. For lower values of T , the velocity distribution function becomes Maxwellian. The theoretical calculations agree well with numerical Direct Simulation Monte Carlo, to validate our theory.